A macrocyclic tetranuclear ZnII complex as a receptor for selective dual fluorescence sensing of F− and AcO−: effect of a macrocyclic ligand. (5th August 2019) - Chakraborty, Tonmoy; Dasgupta, Sanchari; Bhattacharyya, Arghyadeep; Zangrando, Ennio; Escudero, Daniel; Das, Debasis
Abstract : Fluorimetric detection of F − /AcO − with an additional 'INHIBIT ' logic gate response for F − /H + and AcO − /H + in an aqueous-methanol medium by a 48-membered macrocyclic Zn II -complexDAS has been explored by combined experimental and theoretical study. Abstract : A 48-membered macrocyclic Zn II -Schiff base complexDAS (Dual Anion Sensor) containing protonated imine has been synthesized and characterised. The single crystal X-ray structural analysis reveals a tetranuclear complex cation [Zn4 (LH3 )(NO3 )5 ] 2+ counterbalanced by a [Zn(NO3 )4 ] 2− anion.DAS acts as a dual anion sensor which can selectively detect fluoride and acetate in aqueous methanolic solution by change in UV-vis spectra as well as by fluorescence enhancement. A probable mechanistic pathway has been proposed and DFT calculations corroborate well with the experimental data. The calculated limit of detection for F − and AcO − ions was 0.18 and 1.98 μM, and 0.15 and 1.8 μM from UV and FL data, respectively. Interestingly, DAS behaves as anINHIBIT logic gate with F − /AcO − and H + as inputs. To the best of our knowledge, this is the first example where a macrocyclic Zn-complex serves as anINHIBIT logic gate. Practical utility ofDAS has been explored by successful detection of F − in commercially available toothpaste as well as solid state detection of F − and AcO − .